ANALISIS PENILAIAN PASAR WAJAR SAHAM PASKA KEBIJAKAN INSENTIF PAJAK PT. KALBE FARMA, Tbk. PADA TANGGAL 31 DESEMBER 2010 - , Wisnu Junaidi, S.T., Dra.Wahyu Hidayati, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is aimed to estimate the intrinsic stock value of PT Kalbe Farma,Tbk. after the 5 percent tax incentif policy for qualified public companies.This research is done by using dicounted cash flow and relative valuation methods.. The data used in this research consists of its financial report of PT Kalbe Farma, Tbk. which has been audited for 2007 up to 2010,two of comparable companyâs financial report, comparable companyâs stock price, risk free rate, and other supporting data. The comparable companies are PT Tempo Scan Pasific, Tbk. and PT Mercks Tbk. The financial report is analyzed for determining the financial fundamental condition and counting market value of equity PT Kalbe Farma, Tbk. after insentif tax policy by using Income Based Approach and Market Based Approach. The analys isused is DCF methods which go with the following steps: sales or earnings projection analysis, financial statement projection, free cash flow projection, discountrate(WACC) determination and value estimation. Relative valuation method was started by determining comparable company on the industry, followed by choosing and determining the multiples which will be used to converse book value on relevant variable on PT Kalbe Farma,Tbk. to be estimation of market value of equity. The multiples used are: Price Earning Ratio(PER) and Price to Book Value (PBV). The equity value,based on DCF method is Rp2891,32 and on relative valuation method Rp3173,10 (PER=Rp3112,69 and PBV=Rp 3367,17) and (Price to Sales = Rp 3039,48). Thus, the result of the research shows that its intrinsic value of the stocks on the range Rp3116,75. This result is got by giving 20 percent for Income based Approach and 80percent for Market Based Approach.